THE FOLK WISDOM OF SOUR-FISH FOOD PROCESSING TO PROMOTE THE COMMUNITY GOODS , CASE STUDY : SOUR-FISH CAREER GROUP OF HUAY-MOG VILLAGE AT MOO 3, THA-NGUE, MUANG, NAKORN SI THAMMARAT. - มัทมิฬ ปริฉัตร; เดโชชัย อุดมศักดิ์; ดำรงวัฒนะ จิตติมา; แขน้ำแก้ว เดโช (Journal of MCU Nakhondhat, 2015)
The objective of this research was as follow : 1. to study the folk wisdom of Sour-fish food processing to promote the community goods and 2. to study the guideline for promotion the community goods, Case study : Sour-fish career group of Huay-Mog village at Moo 3 , Tha-ngue , Muang , Nakorn Si Thammarat. This research was qualitative research. The research results found that: The folk wisdom of Sour-fish food processing as follow ; 1) the methods of sour-fish processing that should chosen the freshwater fish because they had so much in Huay-Mog village. They would clean the fish and cut in two then put the intestine out and clean again and kept them in salt solution in the pails to pass the night. After that cleaned them again then mixed with roast-rice and brown sugar and contained them in the jar then preserved to pass 4-5 night before eat , 2) Sour-fish career group had identity technic in processing and good taste that customers had satisfied. The guideline for promotion the community goods as follow ; 1) to promote by social media 2) must continuity produced the goods that same requirement of customers , must had quality objects and cleaned goods 3) must had standard and quality as manufacturing and expired date label together.